Diamond/β-SiC film as adhesion-enhanced interlayer for top diamond coatings on cemented tungsten carbide substrate. Issue 10 (October 2017) - Tian, Qingquan; Huang, Nan; Yang, Bing; Zhuang, Hao; Wang, Chun; Zhai, Zhaofeng; Li, Junhao; Jia, Xinyi; Liu, Lusheng; Jiang, Xin
Abstract: In present work, diamond/ β -SiC composite interlayers were deposited on cemented tungsten carbide (WC-6%Co) substrates by microwave plasma enhanced chemical vapor deposition (MPCVD) using H2, CH4 and tetramethylsilane (TMS) gas mixtures. The microstructure, chemical bonding, element distribution and crystalline quality of the composite interlayers were systematically characterized by means of field-emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), X-ray photoelectron spectrometer (XPS), electron probe microanalysis (EPMA), Raman spectroscopy and transmission electron microscropy (TEM). The influences of varying TMS flow rates on the diamond/ β -SiC composite interlayers were investigated. Through changing the TMS flow rates in the reaction gas, the volume fraction of β -SiC in the composite interlayers were tunable in the range of 12.0%–68.1%. XPS and EPMA analysis reveal that the composite interlayers are composed of C, Si element with little cobalt distribution. The better crystallinity of the diamond in the composite is characterized based on the Raman spectroscopy, which are helpful to deposit top diamond coatings with high quality. Then, the adhesion of top diamond coatings were estimated using Rockwell C indentation analysis, revealing that the adhesion of top diamond coatings on the WC-6%Co substrates can be improved by the interlayers with the diamond/ β -SiC composite structures. Comprehensive TEM interfacial analysis exhibits that the cobalt diffusion is weak from WC-6%Co substrate to the composite interlayer. The homogeneous microcrystalline diamond coatings with the most excellent adhesion can be fabricated on the substrates with the composite interlayer with the β -SiC/diamond ratio of about 45%. The composite structures are appropriate for the application in high-efficiency mechanical tool as a buffer layer for the deposition of the diamond coating.